UV and RP-HPLC Method Development and Validation for Estimation of Cilnidipine - Samantaray, Biswajit; Kanhar, Satish; Nanda, Ashirbad (Current Overview on Pharmaceutical Science Vol. 3, 2023)
The current experiment was designed to develop and validate a simple RP-HPLC methodology for determining Cilnidipine. Cilnidipine was quantified using UV spectroscopy. Action separation of Cilnidipine was achieved by using a C18 column. Mobile phase combination of methanol: water (90:10 v/v) was tense at the flow of 1 ml/min. Detection At 241 nm, detection was carried out. In accordance with the International Conference on Harmonization's (ICH) Q2R1 recommendations, validation parameters were assessed. With a parametric value (r2) of 0.999, the standardization curve for cilnidipine was linear over the range of 2–10 mg/ml. The tactic was noticed to be accurate (101.66% recovery), precise (intraday, 1.65 and inter day, 1.38) and robust (% RSD was calculated to be 0.66, 0.58 and 0.81 for variation in mobile phase composition, wave length and flow velocity respectively) for the analysis of Cilnidipine. The developed method has successfully completed all validation tests and can be used to estimate the presence of cilnidipine in both pharmaceutical formulations and bulk.